Social media at workplace : A case study of employees' productivity at Ranaco Marine Sdn Bhd / Nurul Ainsyah Mamat - Mamat, Nurul Ainsyah (Faculty of Business and Management, 2018)
There was considerable debate among academics and business practitioners on the value of social media usage in the workplace. Some claimed that their use in the workplace was a waste of time while others believe it leads to improvements of employees' productivity. The purpose of this study was to investigate the usage of social media in workplace towards employees' productivity. The independent variables that were used in this study were intrinsic motivation, communication channel, knowledge sharing and intention to use while the dependent variable was employees' productivity. A sample was randomly selected from a population in RANACO MARINE SDN BHD. Statistical analysis and Pearson's correlation was undertaken to ascertain the degree of relationship between the variables. Primary data was collected by use of a questionnaire. The research found both weak and strong positive relationship between the usage of social media at work place and employee productivity.